The disparity between intention and reality: The pre-primary o-class context in three rural young lives communities in Ethiopia - Birhanu, K; Tiumelissan, A; Pankhurst, A (Young Lives, 2021)
Although the 1994 Education Policy highlighted the importance of kindergarten education, early childhood education was restricted to urban areas. The National Early Childhood Care and Education Policy Framework in 2010, led to greater emphasis and commitment which has improved access to pre-primary education especially in rural areas, notably through the provision of a one-year preparatory O-Class. However, inequalities and disparities in access persist. Based on data collected in three Young Lives communities this working paper reviews the recent local context of pre-primary education.